2019
DOI: 10.1038/s41467-019-09499-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human health co-benefits on evaluations of global climate policy

Abstract: The health co-benefits of CO 2 mitigation can provide a strong incentive for climate policy through reductions in air pollutant emissions that occur when targeting shared sources. However, reducing air pollutant emissions may also have an important co-harm, as the aerosols they form produce net cooling overall. Nevertheless, aerosol impacts have not been fully incorporated into cost-benefit modeling that estimates how much the world should optimally mitigate. Here we find that when both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 44 publications
1
67
0
1
Order By: Relevance
“…the positive health effects of co-pollutant reduction) from 'deep decarbonization' policies in the US concluded that these policies could prevent on average 36 000 premature deaths annually from 2016 to 2030, and that the monetized value of the avoided early deaths would surpass the climate benefits of these policies, as quantified by applying the US government's SCC (Shindell et al 2016). Similar findings have been reported globally (Parry et al 2014, Scovronick et al 2019, as well as regionally, e.g. for the European Union (Berk et al 2006) and China (Li et al 2018).…”
Section: Introductionsupporting
confidence: 53%
“…the positive health effects of co-pollutant reduction) from 'deep decarbonization' policies in the US concluded that these policies could prevent on average 36 000 premature deaths annually from 2016 to 2030, and that the monetized value of the avoided early deaths would surpass the climate benefits of these policies, as quantified by applying the US government's SCC (Shindell et al 2016). Similar findings have been reported globally (Parry et al 2014, Scovronick et al 2019, as well as regionally, e.g. for the European Union (Berk et al 2006) and China (Li et al 2018).…”
Section: Introductionsupporting
confidence: 53%
“…Second, consumers may benefit from communications that emphasize the health and environmental benefits of rules that focus on, for example, replacing meat products with tofu or quorn (Watts et al 2015, Scovronick et al 2019. Food products that have positive health impacts tend to be perceived as having positive environmental impacts as well (Gorissen andWeijters 2016, Perkovic andOrquin 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To compute the evolution of temperature used to determine damages (Equation 4) we replace the atmospheric module of DICE by following Scovronick et al 49 and making use of the FAIR model detailed in Miller et al 23 FAIR is a more sophisticated earth science model (ESM) than the native DICE ESM. The two primary innovations over DICE's ESM are that (i) a more comprehensive set of GHGs are explicitly modeled and (ii) the impulse response function to a pulse of emissions is state dependent (i.e., the forcings of CH4, CO2, and N20 for a given atmospheric concentration depend on the concentration of other gases) and through this more accurate.…”
Section: Methodsmentioning
confidence: 99%